Polycystic Ovary Syndrome: Pathophysiology, Risk Factors, and Clinical Management – A Literature Review - Luluk Hermawati; I Made Arya Subadiyasa; Nur Bebi Ulfah Irawati; Hilizza Awalina Zulfa; Nur Ayu Virginia Irawati; Rossa Amelia (JURNAL KEDOKTERAN RAFLESIA, 2026)
Polycystic Ovary Syndrome (PCOS) is a complex endocrine disorder commonly observed in women of reproductive age and is associated with reproductive, metabolic, and psychological disturbances. This article aims to comprehensively review the pathophysiology, risk factors, and clinical management of PCOS based on current scientific evidence. The method employed was a narrative literature review, conducted through a systematic search of scientific articles in PubMed, Scopus, Google Scholar, and ScienceDirect databases. The keywords used included polycystic ovary syndrome, PCOS pathophysiology, insulin resistance, anti-Müllerian hormone, and clinical management. Publications in English and Indonesian from 2015 to 2025 were included. The selected articles comprised original research studies, systematic reviews, and relevant literature reviews. The findings indicate that the pathophysiology of PCOS is multifactorial, involving hormonal alterations, insulin resistance, hyperandrogenism, and dysfunction of the hypothalamic–pituitary–ovarian axis, which leads to chronic anovulation. The main risk factors for PCOS include obesity, insulin resistance, sedentary lifestyle, unbalanced nutritional status, as well as metabolic and genetic predispositions, all of which contribute to the heterogeneous clinical manifestations of the syndrome. The management of PCOS is individualized and multidisciplinary, with lifestyle modification as the first-line therapy, supported by dietary interventions, physical activity, and pharmacological treatment according to clinical indications. This review highlights the importance of an integrated approach in the management of PCOS to improve clinical outcomes and prevent long-term complications.